Risk of major cardiac events following adjuvant proton versus photon radiation therapy for patients with thymic malignancies. (3rd August 2017) - Vogel, Jennifer; Lin, Liyong; Simone, Charles B.; Berman, Abigail T.
Abstract: Background: While often managed with surgery alone, patients with thymic malignancies with high-risk features may benefit from adjuvant radiation therapy but are at risk for late toxicities. Previously, the risk of major cardiac events (MCEs) was reported to increase by 7% per one Gray (Gy) to the heart. In this study, we compare dose to organs at risk (OARs) with intensity-modulated (IMRT) versus proton beam therapy (PBT). We hypothesize a decrease risk of predicted MCEs with PBT. Material and methods: Patients requiring adjuvant therapy for thymic malignancies were treated with double scattered proton beam therapy (DS-PBT). Clinical backup IMRT plans were generated. Predicted MCEs were calculated based on median dose to the heart. A Wilcoxon rank sum test was used for statistical comparisons. Results: Twenty-two consecutive patients were evaluated. DS-PBT resulted in statistically significant decreases in dose to the heart, lungs, left ventricle, esophagus, and spinal cord (all p  ≤ .01). The increase in risk of MCEs from 0 to ≥20 years was lower with PBT (74% versus 135%, p  = .04). Discussion: DS-PBT results in decreased dose to OARs and may reduce the risk of MCEs compared with IMRT. Long-term follow-up is required to assess for clinical benefit from DS-PBT.